2012
DOI: 10.1016/j.mimet.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Gene-centric metagenomics analysis of feline intestinal microbiome using 454 junior pyrosequencing

Abstract: The feline gastrointestinal microbiota have direct influence on feline health and also human health as a reservoir for potential zoonotic pathogens and antibiotic resistant bacterial strains. In order to describe the feline gastrointestinal microbial diversity, fecal samples from cats have been characterized using both culture-dependent and culture-independent methods. However, data correlating total microbial composition and their functions are lacking. Present descriptive study evaluated both phylogenetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
129
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(138 citation statements)
references
References 47 publications
8
129
0
1
Order By: Relevance
“…For example, a recent metagenomic study showed that bacteria may represent as much as 98% of all fecal microbiota in dogs, with Archaea, Eukaryotes, and viruses representing only about 2% (Swanson et al 2011). Similarly, a recent study also used a metagenomic approach and showed that Eukaryotes, Archaea, and viruses were minor constituents (< 3%) of the fecal microbiota in cats, while bacteria represented the great majority (97.8%) (Tun et al 2012).…”
Section: The Composition Of the Gi Microbiotamentioning
confidence: 99%
See 3 more Smart Citations
“…For example, a recent metagenomic study showed that bacteria may represent as much as 98% of all fecal microbiota in dogs, with Archaea, Eukaryotes, and viruses representing only about 2% (Swanson et al 2011). Similarly, a recent study also used a metagenomic approach and showed that Eukaryotes, Archaea, and viruses were minor constituents (< 3%) of the fecal microbiota in cats, while bacteria represented the great majority (97.8%) (Tun et al 2012).…”
Section: The Composition Of the Gi Microbiotamentioning
confidence: 99%
“…However, the exact proportions of each bacterial group vary widely throughout the literature. For example, one study showed that healthy cats and dogs may harbor > 90% of Firmicutes in faeces (Handl et al 2011), while others have shown that these animal species may only harbor ~ 13% (cats) and ~ 35% (dogs) of this phylum also in faeces (Swanson et al 2011, Tun et al 2012. The reasons for these discrepancies (see below) are unknown but may include differences in DNA extraction protocols (Zoetendal et al 2001), intra-stool variability of intestinal microorganisms (Garcia-Mazcorro et al 2009), inter-individual differences (Handl et al 2011), the target region of the 16S rRNA gene (Baker et al 2003), as well as inherent differences among the techniques utilized to characterize the microbiota (Zoetendal et al 2004, Kunin et al 2010.…”
Section: The Composition Of the Gi Microbiotamentioning
confidence: 99%
See 2 more Smart Citations
“…102,121 Similarly, DNA shotgun sequencing of feline fecal samples revealed 97% of sequences as of bacterial origin, 1% from eukaryota, 0.1% from archaea, and 0.1% from DNA viruses. 122 Pyrosequencing of the fungal 18 S rRNA gene reported Aspergillus and Saccharomyces as the most abundant fungal genera in pooled fecal samples of cats. 44 In another study, 76% of dogs were positive for fungal DNA on duodenal biopsies.…”
Section: The Microbiome In the Digestive Tractmentioning
confidence: 99%